Pengembangan Media Gambar pada Materi Mengasihi Sesama Seperti Mengasihi Diri Sendiri Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas IV Tahun Pembelajaran 2024/2025. - Fuspa Esika Manik; Hasudungan Simatupang; Johari Manik; Risden Anakampu; Nisma Simorangkir (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study was to develop and produce effective image media on the material of loving others like loving oneself in Christian Religious Education and Character Education learning for grade IV elementary school Merdeka Curriculum. This study uses a development method with the ADDIE approach model. The research location in North Tapanuli Regency consists of Elementary School 173290 Butar, Pagaran District, Elementary School 173291 Butar, Pagaran District, Elementary School 173292 Butar, Pagaran District, Elementary School 178492 Pagarbatu, Elementary School 174573 Hutaraja. The study was conducted in May - August 2024. Data collection used a validation questionnaire and a response questionnaire. The validation questionnaire was used for language expert lecturers, media experts, and material experts. The response questionnaire was used for PAK teachers for grade IV elementary school and grade IV elementary school students totaling 11 elementary school students for small groups and 76 students for large groups. The data analysis used in this study is qualitative descriptive analysis and quantitative descriptive analysis. The results of this study are in the form of image media products of loving others like loving oneself in the subject of Christian Religious Education and Character Education for grade IV of elementary school, Merdeka curriculum. The results of the study indicate that the products made are valid and suitable to be used as learning media. The assessment is based on validation experts, teachers, and students, namely language experts obtained an assessment percentage of 100% (very valid), material experts 100% (very valid), media experts 100% (very valid), religious teachers 96% (very valid) and finally students in small groups obtained results of 96.9% (very good) and large groups 96.36% (very good).